Euphane triterpenoids of Cassipourea lanceolata from the Madagascar rainforest - Hou, Yanpeng (2010)
Fractionation of an ethanol extract of a Madagascar collection of the leaves and fruit of Cassipourea lanceolata Tul. led to the isolation of three euphane triterpenoids 1–3. The (1)H and (13)C NMR spectra of all compounds were fully assigned using a combination of 2D NMR experiments, including COSY, TOCSY, HSQC (HMQC), HMBC and ROESY sequences. The three compounds showed weak antiproliferative activities against the A2780 human ovarian cancer cell line, with IC(50) values of 25, 25 and 32 μM, respectively.